The Role of Clot Waveform Analysis and Related Parameters in the Diagnosis and Treatment of Hemophilia A - Song, Guanghao; Wang, Yangbin; Zhang, Lilei; Xia, Mao (Thrombosis and Haemostasis, 2024)
Background Hemophilia A (HA) is an inherited bleeding disorder caused by a deficiency or defect in factor VIII (FVIII).Methods We investigated the role of clot waveform analysis (CWA) of activated partial thromboplastin time in the diagnosis and therapeutic monitoring of HA. The changes in CWA parameters the maximum clotting velocity (|Min1|), maximum clotting acceleration (|Min2|), and maximum clotting deceleration (|Max2|) were detected among mild, moderate, and severe HA groups.Results As the severity of HA subtypes increased, the levels of |Min1|, |Min2|, and |Max2| progressively decreased (p < 0.05). Receiver operating characteristic curve analysis showed that |Max2| and |Min2| were more effective than |Min1| in distinguishing different types of HA patients, with higher diagnostic efficacy. The standard curves based on Actin FSL reagent for normal and low levels of FVIII:C-|Max2| were established, with R2 values of 0.98 and 0.99, respectively. These curves can be utilized for monitoring during replacement therapies involving full-length recombinant FVIII and B-domain-deleted FVIII. Thirty cases of HA patients utilized the FVIII-|Max2| standard curve to obtain individual pharmacokinetics characteristic parameters. The clearance, half-life (t1/2), time to FVIII:C of 1% above baseline (tt1%), and predicted dosage showed no statistically significant differences compared with one-stage assay (p > 0.05).Conclusion CWA is an economical and practical tool, and its related parameters are associated with the severity of HA. It has promising clinical prospects in predicting FVIII:C levels and individualized treatment when HA patients undergo replacement therapy.
Keywords: clot waveform analysis; factor VIII; hemophilia A; pharmacokinetics; individualized treatment